Magento PHP developer's guide get up and running with the highly customizable and powerful e-commerce solution, Magento - MacGregor, Allan (Community experience distilled, 2015)
This book is written for PHP developers who are familiar with frameworks such as Zend or CakePHP and want to start developing and working with Magento. No prior knowledge of Magento is required.